Theoretical and Legal Bases of the Organization of Bank Guarantee Relations in Commercial Banks - Elboyev Bobur Botirovich (International Journal on Integrated Education, 2022)
In this article, Bank guarantees are one of the most widely discussed issues by economists and lawyers. While economists think about the importance and types of bank guarantees in the formation of payment guarantees, reduction of receivables and payables, commission income, sales of goods, services, lending and other economic relations, lawyers focus on the guarantee of obligations, contractual relations, civil and business law approach. Both approaches imply the need to study bank guarantees. A guarantee is to give something as security. A bank guarantee is a guarantee and surety issued by a bank on behalf of its customers for various business obligations within the framework of certain regulatory documents. Commercial banks provide a bank guarantee that promises to reimburse the customer in the event of default.